2016
DOI: 10.3389/fnhum.2016.00107
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Brain Connectivity in Chronic Pain: A Resting-State fMRI Study in Patients with Rheumatoid Arthritis

Abstract: Background: Rheumatoid arthritis (RA) is commonly accompanied by pain that is discordant with the degree of peripheral pathology. Very little is known about the cerebral processes involved in pain processing in RA. Here we investigated resting-state brain connectivity associated with prolonged pain in RA.Methods: 24 RA subjects and 19 matched controls were compared with regard to both behavioral measures of pain perception and resting-resting state fMRI data acquired subsequently to fMRI sessions involving pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 32 publications
3
61
0
1
Order By: Relevance
“…The PFC is a major component of the mesolimbic circuit, which affects several structures involved in pain perception, motivational drive, substance seeking, and anxiodepressive states (55)(56)(57)(58)(59)(60)(61). A resting-state functional magnetic resonance imaging study with patients with rheumatoid arthritis revealed that prolonged pain states are associated with increased connectivity between the insula and the PFC (62). Using functional magnetic resonance imaging, Baliki et al demonstrated that chronic back pain results in increased PFC activity, and this activity is strongly related to pain intensity (63).…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…The PFC is a major component of the mesolimbic circuit, which affects several structures involved in pain perception, motivational drive, substance seeking, and anxiodepressive states (55)(56)(57)(58)(59)(60)(61). A resting-state functional magnetic resonance imaging study with patients with rheumatoid arthritis revealed that prolonged pain states are associated with increased connectivity between the insula and the PFC (62). Using functional magnetic resonance imaging, Baliki et al demonstrated that chronic back pain results in increased PFC activity, and this activity is strongly related to pain intensity (63).…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…Several studies included in this review investigated the sensorimotor cortex rather than the M1. [23][24][25]37,102 It is possible that heterogeneity in the brain region being investigated (ie, sensorimotor vs M1) contributed to the inconclusive findings of this review.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…Increased SN -DMN connectivity is also a result widely reported within the chronic pain literature. For example, increased connectivity between the DMN and the insula has been described in patients with diabetic neuropathic pain (Chen et al, 2013) and patients with rheumatoid arthritis (Flodin et al, 2016). Increased insula-DMN coupling decreases after treatment in fibromyalgia patients and is associated with a reduction in pain (Napadow et al, 2010).…”
Section: Connectivity Decreases Between Vmpfc and Pcc And Increases Bmentioning
confidence: 99%